2019
DOI: 10.1002/acr.23739
|View full text |Cite
|
Sign up to set email alerts
|

How Do Health Literacy, Numeric Competencies, and Patient Activation Relate to Transition Readiness in Adolescents and Young Adults With Rheumatic Diseases?

Abstract: Transition readiness in AYA patients as measured by TRAQ is associated with female gender, older age, and higher patient activation. Though gender and age are non-modifiable, interventions to boost patient activation represent a promising opportunity to improve transition readiness and outcomes. This article is protected by copyright. All rights reserved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 18 publications
(39 reference statements)
2
29
0
Order By: Relevance
“…Our findings were similar in reference to the score in communication with providers. This finding is comparable to a recent study showing patient activation (including the subdomain of chronic self-management) was associated with higher scores on Transition Readiness Assessment Questionnaire in AYAs with rheumatic diseases (Lazaroff et al, 2018). Considering that young adult patients are closer to the time of transferring from pediatric to adult care, or the time that they have to be responsible for their own care, this finding highlights the importance of interventions and accommodations as early as adolescence to optimize outcomes of self-management and HCT skills long term.…”
Section: Discussionsupporting
confidence: 86%
“…Our findings were similar in reference to the score in communication with providers. This finding is comparable to a recent study showing patient activation (including the subdomain of chronic self-management) was associated with higher scores on Transition Readiness Assessment Questionnaire in AYAs with rheumatic diseases (Lazaroff et al, 2018). Considering that young adult patients are closer to the time of transferring from pediatric to adult care, or the time that they have to be responsible for their own care, this finding highlights the importance of interventions and accommodations as early as adolescence to optimize outcomes of self-management and HCT skills long term.…”
Section: Discussionsupporting
confidence: 86%
“…This finding is supported by the literature on pediatric chronic disease management where self-efficacy has been found to have a positive effect on chronic disease self-management (Noser, Huffhines, Clements, & Patton, 2017;Rhee, Belyea, Ciurzynski, & Brasch, 2009;Smith et al, 2018). Self-efficacy is an important concept to consider when 2015Rheumatology Diseases Carlsen 2017IBD** Dwyer-Matzky 2018MCD  Eaton 2017MCD  -Eluri 2017Eosinophilic esophagitis/ eosinophilic gastroenteritis Kidney transplant Fredericks (2010) Liver transplant Gilleland (2011) Kidney Transplant     Gilleland Marchak 2015Kidney Transplant    Gray 2015IBD Grimsby (2016) Neurogenic bladder Gumidyala 2018IBD  Gutierrez-Colina 2017Pediatric Transplant Haarbauer-Krupa 2019MCD   Hart 2017MCD Javalkar 2014Chronic kidney disease Javalkar 2016MCD Jensen 2017MCD Johnson 2015MCD Lazaroff (2018) Juvenile Idiopathic Arthritis Mackie 2016Heart disease/ transplant McPherson (2009) Sickle cell disease Nazareth 2016MCD Pakdeeprom 2012MCD Rosen 2016IBD Sawicki 2014MCD -Speller-Brown 2015Sickle cell disease   Stewart 2017Heart disease   Szalda 2017Cancer Treadwell (2016) Sickle cell disease Uzark (2015) Heart disease Whitfield ( designing transition readiness interventions, because it encompasses disease self-management and the knowledge and skills needed to independently navigate the health care system. Adolescent and young adult's responsibility for disease management, disease-specific knowledge, perceived barriers to medication adherence, and parental involvement in disease management were also found to be significantly associated with transition readiness.…”
Section: Discussionmentioning
confidence: 99%
“…Four studies did not find a significant relationship between age and transition readiness in youth with inflammatory bowel disease (Carlsen et al, 2017), eosinophilic esophagitis/eosinophilic gastroenteritis (Eluri et al, 2017), kidney transplants , or neurogenic bladders (Grimsby et al, 2016). Seven studies found that female youths with a variety of chronic diseases had statistically significantly higher transition readiness scores (Eaton et al, 2017;Gray et al, 2015;Hart et al, 2017;Javalkar et al, 2014Lazaroff et al, 2018;. Additionally, females with sickle 2015Sickle cell disease  --Stewart 2017Heart disease  -Szalda 2017Cancer Treadwell (2016) Sickle cell disease cell disease or heart disease had higher self-management behavior scores, indicating they were more prepared for transition to adult care (McPherson et al, 2009;Stewart et al, 2017).…”
Section: Demographic and Ecological Factorsmentioning
confidence: 97%
See 2 more Smart Citations